Penerapan Pajak Penghasilan Pasal 22 Atas Pembelian Barang Di Badan Narkotika Nasional Kabupaten Mandailing Natal - Nadiyah Diyanah Nasution; Rizqy Fadhlina Putri; Debbi Chyntia Ovami; Indra Fauzi; Ardhansyah Putra Hrp (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2024)
This research was carried out at the National Narcotics Agency (BNN) Mandailing Natal Regency.The purpose of this research is to determine the application of Income Tax (PPh) Article 22 on theprocurement of goods at the National Narcotics Agency (BNN) Mandailing Natal Regency bycomparing the current regulations, namely Law Number 36 of 2008 concerning the fourth amendmentto the Law. Number 7 of 1983 concerning Income Tax. The data used in this research is data for theyear 2023. Data collection used interview and observation techniques. The data analysis techniqueuses descriptive statistical analysis techniques with the documents used in the form of: tax assistantbook, budget realization report, details of working unit working papers and proof of tax collection.Based on the results of the research conducted, it can be concluded that the application of IncomeTax (PPh) Article 22 on the procurement of goods at the National Narcotics Agency (BNN)Mandailing Natal Regency is in accordance with Law Number 36 of 2008 concerning the fourthamendment to Law Number 7 of 2008 1983 concerning Income Tax.